2005
DOI: 10.1071/wr04126
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat use and foraging behaviour of Sminthopsis youngsoni (Marsupialia:Dasyuridae) in arid central Australia

Abstract: In this study, fluorescent pigment tracking was used to determine the microhabitat use and foraging behaviour of a small insectivorous marsupial, Sminthopsis youngsoni (the lesser hairy-footed dunnart), in the dunefields of the Simpson Desert, south-western Queensland. In total, 25 successful trails were traced over the duration of this study, between March 1996 and April 1998. Nocturnal foraging trails were identified, then the distance travelled by the dunnart through each microhabitat type (nine in all) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…These preferences are consistent with published information on habitat use in each species (e.g. Dickman et al ; Haythornthwaite ; van Dyck & Strahan ; Pavey et al ; Waudby & Petit ; Molyneux et al ).…”
Section: Discussionsupporting
confidence: 90%
“…These preferences are consistent with published information on habitat use in each species (e.g. Dickman et al ; Haythornthwaite ; van Dyck & Strahan ; Pavey et al ; Waudby & Petit ; Molyneux et al ).…”
Section: Discussionsupporting
confidence: 90%
“…As S. youngsoni is a carnivorous food generalist [49] that appears to be largely unaffected by higher predation risk in open habitat [50], we had not expected this species to be affected strongly by grazing. However, as it forages preferentially near spinifex hummocks [51], it may have benefited from the less-trampled spinifex cover in the lightly grazed areas rather than from differences in the grazing regime per se . Other species of dasyurids have been shown to be tolerant of grazing [52] or to decline only in heavily grazed sites [53].…”
Section: Discussionmentioning
confidence: 99%
“…In simplified models, foragers closely track food resources across patches, and choose patch(es) that maximize fitness, resulting in an ideal, free distribution of individuals that mirrors food distribution (Fretwell and Lucas 1970). Several empirical studies have demonstrated that animals occur more frequently or in greater numbers in habitat patches with more abundant food, and for some animals food abundance is the key determinant of distribution (Rey 1995, Haythornthwaite 2005, van Gils et al 2006). However, the correlation between food and distribution of other animals is weakened by diverse factors, such as predation, social interactions, climate, or attempts to forecast future conditions (Marra 2000, Telleria and Perez‐Tris 2007).…”
mentioning
confidence: 99%